Las competencias emocionales en los procesos de inserción laboral - Pérez Escoda, Nuria; Ribera Cos, Anna (REOP - Revista Española de Orientación y Psicopedagogía, 2014)
RESUMEN Este trabajo presenta un estudio basado en la evaluación y desarrollo de las competencias emocionales en los procesos de orientación y formación de personas desempleadas. Se presenta una experiencia realizada en el marco de una investigación entre el Centro IG-NOVA Ocupació de l’Ajuntament d’Igualada y el GROP (Grup de Recerca en Orientació Psicopedagògica) de la Universidad de Barcelona. Esta investigación muestra como el conocimiento y desarrollo de las competencias emocionales permite afrontar con mayor eficacia los procesos de inserción laboral. Se ha aplicado el (QDE-R) cuestionario para la evaluación de las competencias emocionales de adultos a un grupo de 46 personas adultas en situación de desempleo y con un nivel de formación medio-bajo. A partir de los resultados se exponen las aplicaciones derivadas de esta evaluación para un grupo de desempleados usuarios del Servicio Local de Ocupación. ABSTRACT This paper presents a study based on the evaluation and later development of the emotional competences in career guidance processes for jobseekers. This study has been carried out within research framework done by the Center IG-NOVA Ocupació of the council of Igualada and the GROP (Grup de Recerca in Orientació Psicopedagògica) (Group of Research in Psychopedagogic Guidance) of the University of Barcelona. This study shows how knowledge and development of emotional competences allow to more effectively face the processes involved in job seeking. The (QDE-R) inventory was used to evaluate emotional competences in a group of 46 unemployed adults with a lower to middle level of education. All 46 jobseekers were registered within the local unemployment agency. The QDE-R measures five dimensions of the emotional competences: emotional conscience, emotional regulation, emotional autonomy, social skills, lifelong-learning skills and well-being. The results provided with an outline to support the abovementioned jobseekers group. Such jobseekers support was provided for both individuals and the whole group. Whenever individual support was provided, the focus was on those skills more likely to be developed by the individual. At the same time, there was also a strong emphasis to enhance those previously existing skills in order to help individuals in their job-seeking process. The average score of the group can provide with what dimensions must be prioritized when designing a group development program.